Malaria in Pregnancy: A Holistic Review and Approach to Laboratory Findings, Management and Outcomes - Tigor P. Simanjuntak; Giovanni A. Simbolon; Novita Hermanus; Nadya R. Permata; Clarissa Agdelina (Fakultas Kedokteran Universitas Kristen Indonesia, 2019)
Abstract Malaria is an infectious disease caused by protozoa of the genus Plasmodium, transmitted by the bite of female mosquitoes Anopheles. Malaria can infect various populations including pregnant women. The incidence of malaria in pregnancy is quite high especially in tropical - endemic regions such as Indonesia, Papua New Guinea, Nigeria, West Africa and Sudan. It happens because there is no enhanced control activities such as two prevention approaches advocated by the WHO, as well prevention intermittently with sulfadoxine- pyrimethamine (SP) and the treatment of malaria during pregnancy. There are several factors that influence the high prevalence of malaria such as mosquito vectors, malaria parasites, human hosts and environment. As a result of the presence of malarial parasites in the placenta appear serious adverse outcomes to the mother, fetus and newborn. Malaria can be diagnosed with microscopy, rapid diagnostic test (RDT), and polymerase chain reaction (PCR).The firstline treatments recommended by the WHO in the second and third trimester of pregnancy are artemisinin-based combination treatments (ACT).Keywords: Malaria, pregnancy, laboratory findings, management, outcomes Abstrak Penyakit malaria merupakan infeksi yang disebabkan oleh genus Plasmodium, yang ditularkan melalui gigitan nyamuk Anopheles betina. Malaria dapat menginfeksi berbagai populasi termasuk perempuan hamil. Insidens malaria dalam kehamilan cukup tinggi terutama di wilayah tropis - endemik seperti Indonesia, Papua Nugini, Nigeria, Afrika Barat, dan Sudan. Hal itu terjadi karena ketiadaan penanggulangan/pencegahan seperti yang dianjurkan WHO yaitu pemberian sulfadoxine- pyrimethamine (SP) intermiten dan pengobatan malaria dalam kehamilan. Ada banyak faktor yang berperan terhadap kejadian malaria yakni nyamuk sebagai vektor, parasit malaria, manusia sebagai pejamu dan lingkungan yang juga berperan terhadap kejadian malaria dalam kehamilan. Malaria dalam kehamilan berakibat serius trehadap ibu, janin dan neonatus. Diagnosis dapat ditegakkan secara mikroskopi, rapid diagnostic test (RDT), dan polymerase chain reaction (PCR). Pengobatan lini pertama yang direkomendasikan oleh WHO pada trimester ke dua dan ketiga kehamilan adalah kombinasi artemisinin (artemisinin-based combination treatments - ACT).Kata kunci: Malaria, kehamilan, pemeriksaan laboratorium, tatalaksana, luaran